1986
DOI: 10.1111/j.1471-0528.1986.tb08017.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of Citanest with Octapressin for relief of pain associated with laser vaporization of the cervix

Abstract: Summary. Fifty women undergoing laser vaporization of the cervix for cervical intraepithelial neoplasia were randomly allocated to one of two groups. In one group the patients received no anaesthesia, in the other the ectocervix was infiltrated with 2 ml of Citanest with Octapressin (prilocaine 3% with 0.03 i.u./ml. of felypressin) immediately before the procedure. The pain experienced by each group was assessed immediately after treatment by visual analogue and verbal rating scales. The pain experienced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…Prilocaine with felypressin causes statistically significant fewer side effects like feeling faint and shaking; however, the blood loss is greater than that occurring with lignocaine and adrenaline [6]. There is evidence to support local anaesthetic use to reduce postoperative analgesic requirements in large loop excision of transformation zone and episiotomies [7,8] There is some evidence to suggest the same in pelvic floor surgery, but the data are not very robust [9].…”
Section: Discussionmentioning
confidence: 94%
“…Prilocaine with felypressin causes statistically significant fewer side effects like feeling faint and shaking; however, the blood loss is greater than that occurring with lignocaine and adrenaline [6]. There is evidence to support local anaesthetic use to reduce postoperative analgesic requirements in large loop excision of transformation zone and episiotomies [7,8] There is some evidence to suggest the same in pelvic floor surgery, but the data are not very robust [9].…”
Section: Discussionmentioning
confidence: 94%
“…Of three trials (Dane 2008;Gimpleson 1999;Howells 2000) that reported data on stage, 80 women had CIN 1, 53 had CIN 2, 114 women had CIN 2-3, 60 had CIN 3 with a further 12 having normal histology and seven having missing data or having a different histology. Classification was not reported in nine trials (Doyle 1992;Gilbert 1989;; Grundsell 1984(b); Lee 1986;Lipscomb 2006;Lundvall 1984;Rybo 1972;Sabol 1971).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Included studies-The 12 included trials randomised a total of 1602 women of whom 1512 were assessed at the end of the trials. Of these trials, four were from the UK (Doyle 1992;Gilbert 1989;Howells 2000;Lee 1986), two from the USA (Gimpleson1999; Lipscomb 2006), one from Denmark (Lundvall 1984), three from Sweden ; Grundsell 1984(b); Rybo 1972) and one from Turkey (Dane 2008).The largest trial recruited 230 women (Lundvall 1984), with the smallest recruiting 48 (Gimpleson 1999) participants.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1989), non‐steroid anti‐inflammatory drugs have only a small effect on perceived pain (Al‐Kurdi et al . 1985) and direct infiltration of local anaesthetic reduces pain scores by 40% (Lee et al . 1986).…”
mentioning
confidence: 99%